Dynamic fuzzy logic traffic light integrated system with accident detection and action - Taha Alshaikhli, Imad Fakhri; Alkandari, Abdulrahman (IIUM Press, International Islamic University Malaysia, 2017)
The increase of vehicular traffic in the cities is a major concern for the Traffic Management Systems worldwide. The way traffic flow is regulated in the cities directly or indirectly affects the citizen’s life. Thus there is need to optimize and regulate the flow of the traffic effectively to meet the ever increasing demand. This book takes an innovative approach in solving the congestion related to the vehicular traffic, firstly by minimizing the wait time for the vehicles at traffic lights depending on the volume of the traffic and secondly by devising a solution to determine the exact location of the roadblock (caused by an accident or a vehicle breakdown).